Afterword: the utopianisation of bureaucracy - Mathur, N (Wiley, 2020)
Utopia, from the ancient Greek ‘ou‐topos’ (‘not a place’ or ‘nowhere’), quite literally refers to a place that is not there. Perhaps this emphasis on utopia as place is most starkly present in Thomas More’s 1516 Utopia which was an island. Bureaucracy, a combination of the French word bureau (desk or office) and the Greek word kratos (rule), also originated as a form of rule or political power that is embedded in place – a desk, an office. These two types of non‐places have, up until now, been kept largely separate. The Weberian disenchantedness and the ‘iron cage of modernity’ that is most commonly associated with bureaucracy are normally considered a far cry from the desirability implicit in non‐place places and states of being that are utopias. In this act of putting utopias in conversation with bureaucracy and, in fact, considering utopianisation simultaneously a process and an ideal that forms the foundation of international organisations, this collection makes a series of intellectual manoeuvres that I briefly touch on as a focus on scale (the international/national/local); bureaucratisation and utopianisation as processes rather than states‐of‐(non‐)being; methodological hooks; imaginaries of bureaucracy; and the value of comparison.